(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper is entitled “Friends for Life: A Study on Bruce Cameron’s A Dog’s Purpose” is a brief sketch of the companionship between a Dog and a Man. However, this paper flings to bring the role dogs to play in every aspect of human life. Naturally, some Dogs are considered for their loyalty, faithfulness, and love towards their companions. William Bruce Cameron is an American author, columnist, and humourist who is most famous for his novel A Dog’s Purpose, which spent 19 weeks on the New York Times bestseller list. The novel signifies that every dog has a purpose, just as every human does. Eventually, it describes the relationship between man and dog by laying stress on the values of amity with fellow human beings. Thus, the paper examines the love shared by canines and their people from the canine’s point of view. Cameron’s puppy protagonist takes readers on a journey through his life, or rather, lives, because this extraordinary dog lives and dies several times, always searching for his life’s purpose.